Rekonstruksi Pembelajaran Menulis Berbasis Wacana Gender dengan Pendekatan Persidangan - Rangga Asmara (Universitas Tidar, 2017)
Teaching writing based on gender discourse is designed to make the creative writing process is free from discriminating, strereotyping, and marginalizing aspects, which later has negative effects for particular gender. In reality, this process focuses on the teachers’ effort in reconstructing teaching writing based on the conferencing approach. This approach is based on the guided writing process between peers and between students and teachers. This creative writing process is interfered by gender discourse. In this class, the system is affected by characters and shaped by the writer’s character in giving his/her perspectives about male-female roles so there will be no marginalized, discriminated, and labelled groups. This study uses quasi experimental research design. This study aims at finding out the model teaching writing which based on gender discourse and conferencing approach. The procedure of this studi is based on the R2D2 model which has three steps: (1) defining, (2) planning and developing, (3) and disseminating. The data of this study cover qualitative and quantitative data. The qualitative data are analyzed by using domain analysis technique with critical and reflective principles, while the quantitative data are analyzed by statistic analysis techniques with t-test. This study results teaching writing model which based on gender discourse and conferencing approach, such as (1) syllabus, (2) lesson plan, (3) learning materials/text book, (4) evaluation instruments, (5) teaching writing guide. This covers model teaching writing for (a) exposition text, (b) narrative text, and argumentative text. Based on the data analysis, the three models of teaching writing are effective and improve the PBSI (Department of Indonesian Education and Literature) Students’ writing skills at Tidar University.Keywords: conferencing approach, teaching writing, writing model